The Effects of Initial Rehabilitation Exercise on Range of Mo-tion, Muscular Strength, and Muscle Pain after Surgery for Oste-ochondritis Dissecans of the Humeral Capitellum in Middle and High School Baseball Players - Jung-sik Seo; Jin Ho Yoon (Tehran University of Medical Sciences, 2021)
Background: This study evaluated the effects of a 4-week initial rehabilitation program in middle and high school baseball players who underwent removal of a loose body from osteochondritis dissecans of the capitellum humerus. Methods: Middle and high school baseball players with osteochondritis dissecans of the capitellum humerus were enrolled in this study. Each had more than 3 yr of experience and had undergone arthroscopic removal of loose bodies from the same expert at Kim's Orthop Special Clinic in Seoul. The initial exercise rehabilitation program was based on a two-stage program. Body composition, range of motion of flexion and extension in the elbow and wrist joints, grip strength, and subjective pain scale were measured before and after rehabilitation. To assess the differences between groups, we used a two-way analysis of variance. Results: The range of motion for flexion and extension of the elbow and wrist joints, grip strength, and score on the visual analog scale each were significantly improved following the 4-week program (P<0.001), had an interactive effect in time × group (P<0.001), and had significance between groups (P<0.05). Conclusion: The 4-week initial rehabilitation exercise program might improve the overall range of motion of the elbow joint and has a positive therapeutic effect on grip strength and visual analog scores. However, future well-designed studies with more subjects and multicentric research groups are necessary for verification.